Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1177/002200277301700208
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Payoff Structure and Cooperative Behavior in the Prisoner's Dilemma Game

Abstract: This study compares the effect of a standard symmetric Prisoner's Dilemma game and an asymmetric Prisoner's Dilemma game on choice behavior. The two types of Prisoner's Dilemma games were crossed with two sets of payoff matrices, thus generating four experimental conditions. It was predicted that subjects in the asymmetric game condition would manifest less cooperative behavior than subjects in the symmetric game condition. This effect would be due primarily to the significantly lower amount of cooperation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…Based on Pruitt's considerations on integrative solutions and the experimental results by Schellenberg (1964), Sheposh and Gallo (1973) and Talley (1974), occasional defection of low-type players in ASYM might be tolerated to a greater 34 A corresponding Fisher-Pitman permutation test yields (p ≤ 0.014; one-sided) for SYM vs. ASYM (p ≤ 0.072; one-sided) for HIGH vs. ASYM, (p ≤ 0.011; one-sided) for LOW vs. ASYM and (p ≤ 0.351; two-sided) for LOW vs. HIGH. extent than defection in the SYM treatments.…”
Section: Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Pruitt's considerations on integrative solutions and the experimental results by Schellenberg (1964), Sheposh and Gallo (1973) and Talley (1974), occasional defection of low-type players in ASYM might be tolerated to a greater 34 A corresponding Fisher-Pitman permutation test yields (p ≤ 0.014; one-sided) for SYM vs. ASYM (p ≤ 0.072; one-sided) for HIGH vs. ASYM, (p ≤ 0.011; one-sided) for LOW vs. ASYM and (p ≤ 0.351; two-sided) for LOW vs. HIGH. extent than defection in the SYM treatments.…”
Section: Supportmentioning
confidence: 99%
“…The second series of experiments did not yield statistically significant differences between symmetric and asymmetric games. Sheposh and Gallo (1973) ran symmetric and asymmetric experiments. The asymmetric game produced less cooperative behavior than the symmetric game (31.1% vs. 39.2%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies using the prisoner's dilemma paradigm (PDG) have found that negotiators with equal power were more likely to make cooperative choices, resulting in higher joint gains, than those with unequal power (McClintock, Messick, Kuhlman, and Campos 1973;Sheposh and Gallo 1973). Power has also been explored by examining the effects of BATNAs (Best Alternative to a Negotiated Agreement) on dyadic negotiations.…”
mentioning
confidence: 99%
“…On the other hand, when subjects have di¤erent (asymmetric) information, they may feel a sense of unfairness, which decreases the incentive to coordinate. Indeed, several past studies show that asymmetric payo¤s reduce the rate of cooperation in the prisoner's dilemma game (Sheposh and Gallo [1973], Ahn et al, [2007], Beckenkamp, Henning-Schmidt, and MaierRigaud [2007]). These studies consider asymmetric payo¤s, not asymmetric information, but…”
Section: Discussionmentioning
confidence: 99%